What is your language? - Leventhal, Debra; Wellington, Monica (New York : Dutton Children's Books, 1994)
Emphasizes that many different languages are spoken in different parts of the world, giving examples from French and German to Arabic and Spanish.
K-3
K-3
Publisher's Weekly
Keywords: Language and languages; Language and languages